Improving the cold tolerance of false codling moth, thaumatotibia leucotreta, for better performance in a sterile insect release programme - Daniel, Claire Ashleigh (Rhodes University, Faculty of Science, Department of Zoology and Entomology, 2017)
The false codling moth (FCM), Thaumatotibia leucotreta (Meyrick) (Lepidoptera: Tortricidae) is a major pest of citrus and other important crops in Sub-Saharan Africa. The introduction of a sterile insect technique (SIT) programme for FCM in South Africa has proven to be very effective in the control of FCM. The objective was to flood citrus orchards with large numbers of sterile males resulting in a ratio of at least 10 sterile to 1 wild moth, increasing the probability of a female moth mating with a sterile male. This target is often achieved and the programme is generally successful, however there are some challenges regarding this programme. The mass rearing environment, artificial diet, handling methods and irradiation have an impact on sterile insect quality as environmental differences between the rearing facility and field, influences the insect phenotype and competitiveness. This is evident as wild male moths can theoretically actively fly at a temperature of 12°C and laboratory-reared sterilized moths, due to the radiation treatment, appear unable to fly below 20°C. As a consequence, sterile males are out-competed by wild males during the cooler months of the year. This is detrimental to the SIT programme as FCM do not undergo diapause, meaning they are active during winter and will still reproduce. Therefore, to maximize the effect of the SIT programme, it is vital to increase the flight ability of mass reared sterile males at lower temperatures. Various studies have shown that by adding cryoprotectants to the basic laboratory diets increases the cold tolerance of certain insects and thus may allow them to be mobile at lower temperatures, however it imperative that any chemical used to augment the commercial diet of the insect has no negative effects on the insect physiology and development. To investigate this detail for FCM, five generations of FCM were reared on diets augmented with various known insect cryoprotectants. These augmented FCM were subsequently used in experiments designed to determine firstly, if the cryoprotectants had a positive result on the cold tolerance of the FCM, and secondly, if they had any adverse effects on other physiological aspects such as duration of development. Laboratory trials indicated that the flight ability of male FCM was improved when larvae were reared on diets augmented with trehalose and cholesterol (with an average of 40 % of cholesterol and trehalose augmented males that flew at 15 °C where 0 % of the control flew). Results obtained during the field trials support the laboratory results as there was a significant increase in the number of trehalose augmented moths caught in the field during March and July (winter). Results also showed potential for cholesterol to be used as an additive. Other important findings show that both cholesterol and trehalose have no negative impacts on developmental rate, pupal size, and egg production and viability. Trehalose was found to increase the pupal mass of male and female FCM, as well as the number of eggs laid per female. Cholesterol was found to increase developmental rate and the number of eggs laid. The main findings of this study were that diet additives could improve the massrearing of FCM for SIT and the competitiveness of the males, especially at lower temperatures. However, the additives were expensive and cost could well be a constraint to the wide scale implementation of the new technology.
Keywords: Cryptophlebia leucotreta -- South Africa; Cryptophlebia leucotreta -- Reproduction -- Effect of temperature on; Cryptophlebia leucotreta -- Biological control -- South Africa; Citrus -- Diseases and pests -- Biological control -- South Africa; Insect pests -- Biological control -- South Africa; Insecticides; Citrus fruit industry -- South Africa